Enhanced construction of a bivalent adenovirus-based vaccine for preventing childhood pathogens: Human respiratory syncytial virus and norovirus - Ying-Chin Chen; Nai-Hsiang Chung; Yu-Ching Lin; Shu-Ling Yu; Chia-Chyi Liu; Yen-Hung Chow (SLAS Technology)
To impede the spread of respiratory syncytial virus (RSV) and norovirus (NoV) in children, we developed novel recombinant adenoviruses expressing RSV fusion (F) and NoV VP1 proteins driven by different promoter elements (EF1α, SV40, and CMV), resulting in Ad-F/E/NoV, Ad-F/S/NoV, and Ad-F/C/NoV, respectively. The expressed F can be recognized by postfusion-specific antibody targeting to site II and prefusion-specific antibodies targeting to sites V and Ø in the Ad-F-infected cells. However, NoV VP1 is only expressed in Ad-F/E/NoV and Ad-F/C/NoV-infected cells. Intraperitoneal two-dose with monovalent Ad-F and all three bicistronic Ads individually in rodents induced anti-F neutralizing antibodies similarly. Ad-F/C/NoV and Ad-F/E/NoV but not Ad-F/S/NoV significantly induced NoV VP1-specific IgG. The serum from Ad-F/C/NoV-immunized subjects elicited superior anti-NoV activity, as evidenced by reduced binding of NoV VLPs to histo-blood group antigens. Ad-F/C/NoV and Ad-F/E/NoV-immunized mice exhibited elevated cellular immune-mediated splenic IFN-γ and IL-4 secretions. In the RSV challenge study, pulmonary virions were significantly decreased during the vaccination with each of the three bicistronic Ads, confirming their efficacy in preventing RSV infection. Finally, the mucosal (intranasal) immunization in mice with Ad-F/C/NoV induced superior anti-RSV and NoV IgA in both serum and vaginal washes specific to RSV and NoV were highly induced. These findings highlight the optimization of an Ad vaccine targeting two pathogens prevalent in childhood. Additionally, the results underscore the utility of mucosal delivery of Ad vaccines as a valuable strategy for public vaccination efforts.